2018
DOI: 10.1080/21548331.2018.1500369
|View full text |Cite
|
Sign up to set email alerts
|

Cost comparison of fibrin sealant versus tack screws for mesh fixation in laparoscopic repair of inguinal hernia

Abstract: Using FS resulted in cost savings in hospitals based on reduced time to complete surgery, hospitalization time post-op, and lower adverse outcomes. Indirect cost savings were also found in favor of FS when comparing the two alternatives from a societal perspective, as patients were able to return to work more promptly in the FS group versus the tack screws group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Compared with endoscopic tack xation, brin glue is cheaper. Moreover, in terms of postoperative management (administration of analgesics), the cost-e cacy of brin is higher, as shown in previous studies [33,34]. Even for groin incisions, brin glue is more expensive than sutures.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Compared with endoscopic tack xation, brin glue is cheaper. Moreover, in terms of postoperative management (administration of analgesics), the cost-e cacy of brin is higher, as shown in previous studies [33,34]. Even for groin incisions, brin glue is more expensive than sutures.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, there has been a shift in research focus toward reducing complication rates, which led to an increased interest in less invasive mesh xation methods. More studies have reported the e cacy of brin glue for inguinal hernias in clinical settings [8][9][10][11][12][13][14][15][16]. Further, basic research comparing xation capabilities between brin glue and tacks or staples and studies on meshes that are compatible with brin glue are advancing [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Open surgery has a lower cost impact with open inguinal hernia repair using glue representing the least costly alternative [ 52 ]. Panda et al [ 53 ] also made a cost comparison between fibrin glue and tacks but only in laparoscopic procedures. In the following study, costs related to surgical time (600 GBP glue, 700 GBP tack), hospitalization time (400 GBP/day glue, 440 GBP/day tacks), seroma occurrence (3.60 GBP glue vs 8.64 GBP tacks) and neuralgia occurrence (0 GBP glue, 19.44 GBP tacks) were compared for a single surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…International guidelines for groin hernia management recommend the use of non-penetrating mesh fixation for hernia repair to reduce postoperative pain [ 1 ]. Previous comparisons between glue and tack mesh fixation in TEP suggested a hospital cost-saving benefit for glue based on reduced surgical operation time, postoperative hospitalization time, and lower rates of adverse outcomes [ 44 ]. According to international guideline management for groin hernias, SGM has proven controversial for open repair, whereas evaluation of laparoscopic approaches is limited due to lack of data [ 1 ].…”
Section: Discussionmentioning
confidence: 99%